THE COMPARISON OF ELEMENTARY CHINESE TEXTBOOKS USED IN UNIVERSITIES IN THAILAND - รัตนชัยไพศาลกุล, ชนิกานต์ (Chinese Language and Culture Journal, 2021)
Nowaday, there were many problems in Chinese language teaching for university level. This study focused on textbook quality and suitability and text selection. The purpose of the study was comparing five basis Chinese textbooks which were used in basic Chinese teaching in universities in Thailand. The textbooks were 1) Hanyu Jiaocheng (汉语教程) 2) Fazhan Hanyu (发展汉语) 3. Chuji Hanyu (初级汉语) 4) Taiguorenxuehanyu (泰国人学汉语) 5) Boya Hanyu (博雅汉语) The textbooks were compared in both qualitative and quantitative by analyzing in five aspects as phonetics, lesson, vocaburary, grammar and excercise. The sugessions, guidance for selection and guidance for Chinese textbook writing for university level were also presented. The result yielded that each textbook had different strenght and weakness as follow; 1) Hanyu Jiaocheng strenght were phonetics, which was suilably distributed, and thier grammars with the compatible excercises yet, the number of the grammars was fewer than other textbooks and the excercises lacked of variety. 2) Fazhan Hanyu had various lessons and the most grammars which was also the most compatible with the curriculum. They also had various form of excercises but thier drawback was lacking elementary vocaburaries. 3) Chuji Hanyu was also strenght in grammar and overall aspects were rather good. 4) Taiguorenxuehanyu strenght were phonetics and elementary grammars and vocaburaries. Various excercises were also included but their grammars were the least compatible with the curriculem. 5) Boya Hanyu presented vocaburaries that were the most compatible with the curriculum but their weakness was the variety of the excercise in phonetics.